THE USE OF AUTHENTIC MATERIALS IN DEVELOPING COMMUNICATIVE COMPETENCE. - Bozorboeva Lobar Alisher qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article examines how authentic materials—texts, audio, video, and visual media not originally created for language learners—enhance learners' communicative competence  in  EFL/ESL  contexts.  Drawing  upon  empirical  studies  and  theoretical discourse,  we  argue  that  authentic  materials  boost  motivation,  cultural  awareness, listening and reading proficiency, and the pragmatic use of language. While benefits clearly outweigh drawbacks, careful task design and balanced integration are necessary to mitigate challenges such as learner frustration or cognitive overload. We recommend a  calibrated  inclusion  of  authentic  materials  (approximately  50  %)  in  curricula  to maximize communicative development.